The Many (Subtle) Ways Parents Game the System: Mixed-method Evidence on the Transition into Secondary-school Tracks in Germany. Issue 2 (April 2019) - Dumont, Hanna; Klinge, Denise; Maaz, Kai
We analyze the subtle mechanisms at work in the interaction between families and schools that underlie social inequalities at the transition point from elementary school into secondary-school tracks in Berlin, Germany. We do so by combining quantitative data from a large-scale survey and assessment study ( N = 3, 935 students and their parents) with qualitative data from in-depth interviews with parents ( N = 25) collected during the 2010–11, 2011–12, and 2012–13 school years. The quantitative analyses show that students from high–socioeconomic status (SES) families were more likely to enter the academic track than were students from low-SES families, even if they performed equally well on a standardized achievement test, had the same grades in school, and received the same track recommendation from their teachers. The qualitative analyses illustrate the many ways in which parents intervene during the transition process, with high-SES parents having particularly effective ways of getting what they want for their children.